Incidence, trends and histopathological pattern of cervical malignancies at BP Koirala Memorial cancer hospital, Nepal. - Pathak, TB; Pun, CB; Shrestha, S; Bastola, S; Bhatta, R (Journal of Pathology of Nepal, 2013)
Background: Cervical cancer is one of the most common gynecological malignant tumors worldwide and the leading cause of death from genital malignancies in women. We evaluate the trends and patterns of cervical malignancies in our institution. Materials and Methods: All the tissue slides of cervical malignancies at the department of pathology at BP Koirala Memorial cancer hospital over a period of 3 years (2009-2011) were retrieved and evaluated. Clinical data were obtained from the medical records. Results: A total of 1955 cases were registered as gynecological malignancies, out of which cervical malignancy constitutes 1341 (68%) cases followed by ovarian malignancies 425 (22%) cases. Only 874 cases were included in this study due to inadequate data retrieval. The age range for cervical cancer was 24 to 92 years with a mean age of 42.5 years. Squamous cell carcinoma (92.56%) was the most common histological type of cervical cancer, followed by adenocarcinoma (4.1%). Conclusion: This study has shown a high incidence of carcinoma of cervix at BP Koirala memorial cancer Hospital. Routine cytological screening of the population for cervical cancers is highly necessary as early detection of premalignant lesions. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 386-389 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7863